Digital Literacy Integration and Teacher Belief in Public Elementary School: Examining Decomposed Theory of Planned Behavior - Khoirul Latifah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
One of the most important aspects of learning in the twenty-first century has been acknowledged: the necessity of using digital technology into instructional materials. With these developments, special abilities are needed by teachers regarding their beliefs to integrate them so that learning can develop according to the provisions of learning objectives, security, and applicable ethics. This study is intended to examine teacher’s belief in digital literacy integration in state elementary school using Decomposed Theory of Planned Behavior. The study was a qualitative study by means of case study research design to obtain a realible understanding of the phenomenon. The data were collected using interview, observation and study documentation. The result indicate that influence teacher’s beliefs in the integration of digital literacy are found from self-efficacy, reseource facilitating condition and technology facilitating condition. Teacher’s efficacy is influenced by teacher training.This situation implies that positive teacher beliefs about digital literacy have a good impact on efforts to integrate digital literacy in learning. This research also strengthens that digital literacy can be maximized if accompanied by the role of policy makers, especially school principals